2020
DOI: 10.1002/fsn3.1886
|View full text |Cite
|
Sign up to set email alerts
|

Effects of kiwi’s pectin methylesterase inhibitor, nanomilling and pasteurization on orange juice quality

Abstract: Citrus is considered the most consumed fruits in many parts of the world especially orange, and the world production of orange in 2018 was estimated to be 75.4 million tons, while in Egypt was estimated to be 3.24 million tons (FAO, 2020). Orange fruits (Balady cultivar, Citrus aurantium) are very important nutritional, industrial, and commercial crop in Egypt (Khedr, 2017). Juice is the main product of orange which consumed either fresh or processed, and in both cases, the need for natural high-quality juice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Pectin methyl esterase is one of the pectic enzymes found in citrus juices and responsible for their quality deterioration through undesirable precipitation of cloud particles. Therefore, the deactivation of this enzyme is required during juice processing to keep juice quality (Bazaraa et al, 2020). Data indicated that the application of UV had no significant ( p ≤ 0.05) effect on PME activity and activities were 1.13, 1.11, 1.12, 1.09 and 1.10 (u/mL) for sample exposed to 0, 15, 30, 45 and 60 min, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Pectin methyl esterase is one of the pectic enzymes found in citrus juices and responsible for their quality deterioration through undesirable precipitation of cloud particles. Therefore, the deactivation of this enzyme is required during juice processing to keep juice quality (Bazaraa et al, 2020). Data indicated that the application of UV had no significant ( p ≤ 0.05) effect on PME activity and activities were 1.13, 1.11, 1.12, 1.09 and 1.10 (u/mL) for sample exposed to 0, 15, 30, 45 and 60 min, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…NPs should be treated as new chemicals requiring new safety assessments before being allowed for use in any consumer product. On 8 October 2020, the European parliament announced the ban of titanium dioxide, referred to as E171, as a food additive because in many foods the proportions of NPs were greater than 50% and not labeled as “nano” [ 175 ]. This ban does not refer to the titanium dioxide added in the packaging material.…”
Section: Discussionmentioning
confidence: 99%
“…The suspension was based in water and the microorganisms that were studied consisted of two Gram-negative bacterial species ( E. coli and P. aeruginosa ) and two fungal species ( P. notatum and A. niger ). In another study, nanomilling was applied in orange juice pulp for the preparation of orange juice [ 175 ]. A slight reduction in the content of ascorbic acid was observed, but at the same time the initial microbial load was decreased and the stability of the juice was enhanced.…”
Section: Applications Of Nanotechnology In the Cosmetics And Food Ind...mentioning
confidence: 99%
“…PME is physiologically released into the juice during processing, and it is considered a juice clarifying enzyme. PME activity, by triggering the formation of "egg-box" structures, causes the precipitation of pectins and cloud loss in juice, one of the major problems in fruit juice manufacturing industries (Bazaraa et al, 2020). The thermal inhibition of PME activity might be a solution but it can negatively affect the nutritional quality of the juice.…”
Section: Pmei In Fruit Development Ripening and Postharvest Fruit Pro...mentioning
confidence: 99%